2022
DOI: 10.1093/nar/gkac920
|View full text |Cite
|
Sign up to set email alerts
|

CARD 2023: expanded curation, support for machine learning, and resistome prediction at the Comprehensive Antibiotic Resistance Database

Abstract: The Comprehensive Antibiotic Resistance Database (CARD; card.mcmaster.ca) combines the Antibiotic Resistance Ontology (ARO) with curated AMR gene (ARG) sequences and resistance-conferring mutations to provide an informatics framework for annotation and interpretation of resistomes. As of version 3.2.4, CARD encompasses 6627 ontology terms, 5010 reference sequences, 1933 mutations, 3004 publications, and 5057 AMR detection models that can be used by the accompanying Resistance Gene Identifier (RGI) software to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
242
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(353 citation statements)
references
References 24 publications
(33 reference statements)
0
242
0
3
Order By: Relevance
“…Gene calling and annotation were performed with the Rapid Annotation using Subsystem Technology (RAST) server ( ) ( Aziz et al., 2008 ) and the SEED viewer framework ( Overbeek et al., 2014 ). In addition, the antibiotic resistance genes of strains are obtained by comparison in the comprehensive antibiotic resistance database ( ) ( Alcock et al., 2022 ). Using the virulence factor database (VFDB, ) ( Liu et al., 2019 ), we identified genome encoded virulence factor (VF) genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene calling and annotation were performed with the Rapid Annotation using Subsystem Technology (RAST) server ( ) ( Aziz et al., 2008 ) and the SEED viewer framework ( Overbeek et al., 2014 ). In addition, the antibiotic resistance genes of strains are obtained by comparison in the comprehensive antibiotic resistance database ( ) ( Alcock et al., 2022 ). Using the virulence factor database (VFDB, ) ( Liu et al., 2019 ), we identified genome encoded virulence factor (VF) genes.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the antibiotic resistance genes of strains are obtained by comparison in the comprehensive antibiotic resistance database (https://card. mcmaster.ca/analyze) (Alcock et al, 2022). Using the virulence factor database (VFDB, http://www.mgc.ac.cn/VFs/main.htm) (Liu et al, 2019), we identified genome encoded virulence factor (VF) genes.…”
Section: Whole-genome Sequencing Analysesmentioning
confidence: 99%
“…In addition, phage genomes were blasted on the GenBank database, and the life cycle of the closest phage homolog was identified. The presence of antibiotic resistance genes and bacterial virulence factor encoding gene in phage genomes was evaluated using CARD [ 29 ] and the VF analyzer on the Virulence Factor Database [ 30 ], respectively. The absence of prophage, from the production strain, was verified in silico using Phaster [ 31 , 32 ] and the absence of temperate phage expression arising from a prophage lacking the replicase gene was assessed by qPCR in the phage preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, all intact prophage sequence were screened for antibiotic resistance genes using the RGI tool v.5.2.1, which uses CARD [ 44 ], exploring perfect, strict, and loose hits, and virulence factors via the Virulence Factor Database (VFDB) [ 45 ]. RGI was installed locally using conda, and the CARD database (v.3.1.4) was downloaded.…”
Section: Methodsmentioning
confidence: 99%